Effects of tractor mounted mulcher blades on tractor vibration while mulching oil palm fronds - Jahun, Bala Gambo; Ahmad, Desa; Mahadi @ Othman, Muhammad Razif; Sulaiman, Shamsuddin (Penerbit MARDI, 2018)
Mulching of oil palm fronds as alternative of waste disposal using the existing blade affects the operators regarding vibration. Three different blades were developed using Solid Works, fabricated and performance compared. Measurement was conducted using Sensor VM 24 vibration meter at the Universiti Putra Malaysia oil palm plantation. Four blades with different lifting angles (60°, 90°, 120°, and 150°), two tractor PTO speeds (540 and 1000 rpm) and three tractor forward speeds (1, 3, and 5 km/h) were the independent variables used. Statistical analysis based on ANOVA test of significance was in Completely Randomized Blocked Design (CRBD) and showed a significance at (P<0.05). Tukey's Studentized Range (HSD) test showed significant difference (P<0.05). The results show minimum vibration was given by the blade with 90o lifting angle. Multiple regressions were used for the relationships between independent variables to predict a model equation for vibration. Linear and quadratic regression coefficient showed a highly significant, P= 0.0001 and the coefficient of determination (R²) = 0.3766 and 0.377 respectively are weak and not fit to predict vibration.